THE IMPACT OF OPHIOLITIC MÉLANGES ON THE GROUNDWATER GEOCHEMISTRY OF NAEEN AQUIFER (CENTRAL IRAN) - Kayhomayoon, Zahra (Ofioliti, 2024)
The management of groundwater resources requires recognizing the natural and human factors affecting water quality and, if possible, controlling, reducing, or eliminating the detrimental effects, if any. In order to investigate the effects of ophiolite mélange on the quantity and quality of water resources in the Naeen region, central Iran, the quantitative data of 34 observation wells in the time span between 2005 and 2020, the qualitative data of 20 groundwater samples from the Naeen aquifer, and 22 samples of groundwater from the Daghe Sorkh aquifer were investigated. Groundwater flow maps, aquifer hydrographs, compositional diagrams (Piper, Stiff, Scholler, and Wilcox diagrams), analytical diagrams, ionic ratios, saturation indices, statistical analyses (correlation matrix, dendrogram, hierarchical cluster analysis), and neural networks self-organizing maps (SOM) were considered for quantitative and qualitative analyse of the Naeen and Daghe Sorkh aquifers. Based on the quantitative investigations of the Naeen aquifer, the drainage of four permanent Qanats located in the south of the ophiolitic massif is affected by structural features (fractures and faults), Cretaceous limestones, and alluvial fans in the northern high-elevation regions of the aquifer. Analyses of the qualitative data showed that cation exchange, carbonate dissolution, and silicate weathering are the dominant processes affecting groundwater chemistry. Alteration and dissolution of peridotites (chiefly dunites and harzburgites) of the ophiolitic complex are responsible for the transfer of magnesium and bicarbonate to the groundwater interacting with the ophiolitic rocks. The fineness of aquifer sediments, and consequently, the increase in residence time, the high amount of evaporation compared to rainfall in the study area, and the return of agricultural water with very high salinity have caused an increase in EC values of the groundwater in the study aquifer.